Bifurcation Analysis of a Model of Cancer - Abdo M. Al-Mahdi; Mustafa Q. Khirallah (European Scientific Journal, ESJ, 2016)
In this paper, we study the bifurcation of a cancer model with completely unknown parameters. The bifurcation analysis of the biologically feasible steady-states of this model will be discussed. It is proved that the system appears to exhibit many cases of bifurcation for some ranges of system parameters. Numerical analysis and extensive numerical examples of the bifurcation for some ranges were carried out for various system parameter values and different initial densities.